Plant Immunity Is Compartmentalized and Specialized in Roots - Chuberre, Coralie; Plancot, Barbara; Driouich, Azeddine; Moore, John P.; Bardor, Muriel; Gügi, Bruno; Vicré, Maïté (Frontiers in Plant Science, 2018)
Root is an important organ for the life of the plant. However, so far little attention has been paid to the defense responses in root as compared to leaves. This review summarizes the current knowledge regarding root defense strategies against pathogens. Studies reviewed here suggest that putative markers of defense responses in leaves are less critical in roots. In addition, a number of studies have demonstrated that immune responses induced in root are tissue-specific suggesting a compartmentalization of defense mechanisms in this organ. In addition, roots are able to activate specific defense mechanisms in response to various elicitors also called stimulators of plant defense (PDS). A deep understanding of the root immune system is particularly important for the future development of new strategies to control root disease and improve crop quality.